Response—Francis M. Gaffney - Francis M. Gaffney (Washington University Law Quarterly, 1971)
Does the social scientist have a role to play in helping judicial decision-makers make more effective and valid decisions? Even when this question is juxtaposed with the skepticism which has characterized the legal profession's attitudes toward the social sciences, the answer would seem to be yes. The research reported here does not bear the imprint of youth, imprecision or changefulness. The studies by Grossman, Schmidhauser and Skogan are indicative of a vital point in the maturation process of any science, the stage at which basic hypotheses and notions are subjected to empirical validation. Those by Burnham, Cook and Fahey are characteristic of a maturing science which has achieved a sufficient degree of internal development to enable its practitioners to turn to problem oriented research. With these two activities going on simultaneously, there will undoubtedly be changes within the social sciences, but the changes that do occur will result in increased maturity. Given these trends within the social sciences, and the law's desperate need for a reliable empirical base, these studies may well harbinger a productive exchange between law and the social sciences.